Morphological Variations of Robusta Coffee As a Response to Different Altitude in Lampung - Erwin Prastowo; Rina Arimarsetiowati (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2019)
The coffee growth is considered to depend, partly, on the environmental condition at which they develop to accomplish both vegetative and generative stages. An exploratory survey in Lampung aimed at investigating the morphological characteristics of 13 Robusta coffee accessions growing on different altitudes.Local superior coffee clones were selected from eight farms, and subjected to identifications. Three key issues were concerned for both quantitatively, i.e. plant components of leaves, branches, and fruits, and qualitatively such as leaves and fruit characteristics, i.e. colour and shape. The analysis shows a similarity of about 60% of total qualitative variable identified among different accessions. The remaining characters are suggested to be more varying such as flush colour, leaf surface, ripe fruit colour, and stipule shape. Furthermore, a quantitative analysis showed a higher level of similarity for fruit characters, i.e. fruit length, -width, and -thickness, and to a slightly lower level for leaf characteristics, i.e. leaf length and -width, and number of productive branches. It was revealed that some variables, i.e. fruit weight; leaf and seed; and canopy characteristics, explaining the morphological variation of coffee throughout the accessions. Furthermore, cluster analysis may indicated a possible similarity of coffee morphologies either from area with different or the same environmental conditions. A high heterogeneity related to environmental conditions, genotypic variations, plant nutritional status, and agronomic practices, which unable to confirm in the present study, may limit the specific conclusions.